Cerebrovascular Disease in the Young Adult: Examining Melatonin’s Possible Multiple Roles - Onaolapo, Adejoke Yetunde (J Exp Neurosci, 2019)
In the last decade or more, there have been reports suggesting a rise in the incidence of stroke in young adults. Presently, it appears that the risk factors associated with the cause of stroke in young adults remain relatively constant across different geographic regions of the world. Moreover, the endogenous rhythm of a neurohormone such as melatonin is known to play certain roles in the modulation of some of the risk factors that are associated with an increased risk of stroke in young people. Whereas animal studies have shown that melatonin plays diverse roles in stroke, only a limited number of human studies examined the roles of exogenous melatonin administration in the prevention of stroke, attenuation of neuronal damage, and improving outcome or well-being in stroke patients. In this review, first we summarize existing studies of stroke in the young adult and then provide insights on melatonin and stroke. Thereafter, we discuss the role of melatonin in models of stroke and how melatonin can be regulated to prevent stroke in young adults. Finally, we highlight the possible roles of melatonin in the management and outcome of stroke, especially in the young adult stroke population.